THE POLICY OF FOREIGN PORTOFOLIO INVESTMENT LIBERALIZATION AND ITS IMPLICATIONS TOWARD THE NATIONAL BANKING POLICY ON GIVING THE CREDIT TO THE SMALL AND MEDIUM ENTERPRISES - Sugeng Ribowo (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2017)
Foreign Portofolio Investment is one of the parts of foreign investment policy,its existence has the important role to the economic development of a country,especially to the developing countries to prevent the deficit of a country.Indonesia is one of developing countries that has implemented the policyrapidly by liberating foreign portofolio investment. This makes the foreignfund flood Indonesia without any control. Its legally caused legislationproduct regulating the kinds of this investment subtancially do not regulatelegal precision between two countries. Therefore, it gives overborrowingimpacts that have to be guaranted by a country in a certain time. Its differentfrom other developing countries determined foreign portofolio investment withthe strong control and given tax disincentive to the investors, such as China,Corea, Thailand and others.The behavior of this policy, is appereant and it cannot be separate fromforeign influence that suggested by International Monetary Fund (IMF) andWorld Bank (WB) as a financial international institution with the basicfinancial globalization. Financial globalization, directly and indirectly hassupported the government policy that is very kind to the foreign intervention.Its evidenced by the dominated legalize by the ownership of foreign stock inforeign right corporation or financial institution (banking) that has implicitlythrough laws. Therefore, foreign portofolio investment has caused themagnetic strength, especially banking institution to get the traget of big gainby buying and selling it to foreigner than distributing of credit to the smalland medium enterprises.This phenomenon, implicates to the change to the policy in the banking sector,banking experienced shifting of vital function that as to be able to allocate thefund source to the society efficienly and effectivetely. The shifting of vitalbanking function, from traditional activity to the non-traditional activity iscaused by the complicated problems like institution, regulation, andglobalization, especially financial globalization. Therefore, the strength of thestate about political economy is the main solution to solve these problems.This research, will be analyzed comprehensively about the Policy of Foreign Portofolio Investment Liberalization and its Implications toward the NationalBanking Policy on Giving the Credit to the Small and Medium Enterprises.Beside, this research will also be explained the relevant policy to solve thevital functions of banking as intermediation institution to the small andmedium enterprises, its influence can be hoped to the financial stability andeconomic development sustainability.Key words: liberalization, foreign portofolio investment, financial globalization, politicaleconomy, national banking